2009
DOI: 10.1093/eurheartj/ehp049
|View full text |Cite
|
Sign up to set email alerts
|

High serum YKL-40 concentration is associated with cardiovascular and all-cause mortality in patients with stable coronary artery disease

Abstract: High serum YKL-40 is associated with MI, cardiovascular and all-cause mortality in patients with stable CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
129
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 31 publications
11
129
7
Order By: Relevance
“…A significant correlation between YKL-40 plasma levels and age has been a matter of agreement (19,20,22,23,25,26,(28)(29)(30) or disagreement (14, 31-34) (like ours) in different studies. Such pros (23,24,35) (like ours) and cons (13,14,19,27) issues are also true in the case of the significant correlation between YKL-40 plasma levels and BMI.…”
Section: Discussionsupporting
confidence: 51%
“…A significant correlation between YKL-40 plasma levels and age has been a matter of agreement (19,20,22,23,25,26,(28)(29)(30) or disagreement (14, 31-34) (like ours) in different studies. Such pros (23,24,35) (like ours) and cons (13,14,19,27) issues are also true in the case of the significant correlation between YKL-40 plasma levels and BMI.…”
Section: Discussionsupporting
confidence: 51%
“…14,18,19 Recently, several clinical studies have described an association between increased YKL-40 levels, and several cardiovascular conditions, myocardial infarction, atrial fibrillation, and mortality. 10,20,21 PEX is a disorder of the extracellular matrix that is frequently related to severe chronic secondary open-angle glaucoma. 2 Extraocular deposition of pseudoexfoliation material has been localized to the connective tissues or septa traversing the organ tissue.…”
Section: Resultsmentioning
confidence: 99%
“…8 Increased serum YKL-40 concentration has been found to be associated with cardiovascular morbidity. 9,10 It has been also displayed that YKL-40 could be used as a biomarker for atherosclerosis at very early stages of cardiovascular diseases. 11 We hypothesized that YKL-40 could have a role in the pathogenesis of PEX.…”
Section: Introductionmentioning
confidence: 99%
“…9 This hypothesis was recently verified in clinical settings in patients with coronary artery disease. 15 Two recent studies demonstrated significantly elevated levels of YKL-40 in patients with type II diabetes as well as a positive correlation with insulin resistance and lipid disturbances. 8,9 This study was carried out to test the possibility that antihypertensive treatment with moxonidine may induce more favorable effects than the dihydropyridine calcium antagonist amlodipine on insulin resistance, serum lipids, uric acid and a new cardiovascular risk marker, YKL-40.…”
Section: Introductionmentioning
confidence: 99%